Parameters of writing research papers by multiple authors: Who writes what to whom? / Ali Derahvasht and Moses Samuel - Derahvasht, Ali; Samuel, Moses (Penerbit UiTM (UiTM Press), 2017)
This study investigated the writing parameters of a research paper by multiple authors who formed a research team in a public university in Malaysia. Drafts of the research paper were produced through the research activities and writings of the participant researchers. By observations, interviews, and textual analysis of drafts, we studied the three main parameters that each written text naturally contains: who wrote the text, what the text was, and to whom the text was written. Participants in the present study comprised a team of researchers from different disciplines. They conducted a project in science, wrote, and published their findings in an on-line journal. The findings indicate that the authentic task of writing a multi-authored research paper by a team of experienced researchers is beyond and more complicated than fulfilling a basic task of writing in the context of a class by a novice student. The experiences through which the participant researchers of this study produced the drafts of the article are greatly valuable for the academics who are planning to publish their findings in the form of an article. This study has implications for teaching of writing academic texts, particularly writing of research papers.